Personal Factors as Correlates and Predictors of Relapse in Nurses With Impaired Practice. Issue 1 (January 2019) - Mumba, Mercy N.; Baxley, Susan M.; Cipher, Daisha J.; Snow, Diane E.
Abstract : Relapse is the unauthorized use of any mind-altering substance, prescribed or not, after an individual has entered treatment for substance use (Darbro, 2011). Among nurses with impaired practice, the 5-year relapse rate is estimated at about 40% (Zhong, Kenward, Sheets, Doherty, & Gross, 2009), and the risk of relapse is highest in the first year of recovery (Clark & Farnsworth, 2006). Many factors influence susceptibility to relapse among nurses including presence of psychiatric comorbidities (Schellekens, de Jong, Buitelaar, & Verkes, 2015), history of criminal background (Zhong et al., 2009), spirituality and religiosity (Allen & Lo, 2010), and receiving prelicensure education in the United States (Waneka, Spetz, & Keane, 2011). The purpose of this study was to examine the correlates and predictors of relapse among nurses and to establish at what point they are most susceptible to relapse. This study was a retrospective secondary data analysis of nurses in Texas with impaired practice. The total number of participants was 1, 553. The time it takes participants to enroll in a peer assistance program is negatively associated with length in program ( p < .001). Conversely, there is a strong, positive, significant relationship between the number of days abstinent and the length in program ( p < .001). More men compared with women ( p = .037) were likely to be employed while participating in the program. Finally, participants who were referred for substance use disorders alone had 55% less risk of relapse. Those who used alcohol as their primary drug of choice had 1.7 times higher risk of relapse.